Inappropriate screening of obstructive coronary artery disease during pre-anesthesia assessment of candidates for non-cardiac surgery - Oliveira,A.C.C. (2021)
Preoperative evaluation in elective surgeries has been associated with successful surgical treatment. However, there is no solid scientific evidence that screening for coronary artery disease (CAD) reduces surgical risk. The aims of this study were to describe the frequency of inappropriate investigation of obstructive CAD induced by pre-anesthetic assessment in individuals without cardiovascular symptoms (candidates for low- to intermediate-risk surgeries) and to evaluate predictors of this conduct. We performed a retrospective evaluation of medical records of anesthesiology services from patients undergoing pre-anesthesia assessment between May 2015 and May 2016, including those with functional capacity ≥4 metabolic equivalents without a diagnosis of heart disease. A total of 778 medical records (47±16 years of age, 62.6% female) were studied. A private hospital performed 50.1% of the surgeries and 60.4% were of intermediate risk. Only 2.7% (95%CI: 1.7-4.1%) were screened for CAD, and 91% of these requests were mediated by cardiology consultations performed during pre-anesthetic testing visits. Factors associated with screening for CAD were hypertension, diabetes, moderate systemic disease (ASA III), cardiac consultation, previous diagnosis of CAD, and admission to a private hospital. Independent predictors were private hospitals (OR: 3.9; 95%CI: 1.3-11.0), ASA III (OR: 5.3; 95%CI: 1.7-16.2), and hypertension (OR: 3.8; 95%CI: 1.5-9.8). The frequency of inappropriate requests for CAD screening in asymptomatic individuals without untreated systemic diseases was low in pre-anesthetic visits. Although infrequent, screening for CAD is more common in the private setting, in patients with poorer health status, and is usually prescribed during cardiology consultation.